2007
DOI: 10.1128/mcb.01439-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Glucocorticoid Receptor β Binds RU-486 and Is TranscriptionallyActive

Abstract: Human glucocorticoid receptor (hGR) is expressed as two alternately spliced C-terminal isoforms, ␣ and ␤.In contrast to the canonical hGR␣, hGR␤ is a nucleus-localized orphan receptor thought not to bind ligand and not to affect gene transcription other than by acting as a dominant negative to hGR␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 41 publications
8
149
2
1
Order By: Relevance
“…2), which suggests that the binding of RU486 to the GR protein does not bring about translocation in the rainbow trout zygote as it appears to do in several mammalian cell lines (murine fibroblast cells: Pariante et al (2001), primate kidney and osteosarcoma cells: Lewis-Tuffin et al (2007), and murine pituitary cells: Peeters et al (2008) and Spiga et al (2011)). Moreover, RU486 does not appear to inhibit cortisolactivated translocation.…”
Section: K1mentioning
confidence: 99%
“…2), which suggests that the binding of RU486 to the GR protein does not bring about translocation in the rainbow trout zygote as it appears to do in several mammalian cell lines (murine fibroblast cells: Pariante et al (2001), primate kidney and osteosarcoma cells: Lewis-Tuffin et al (2007), and murine pituitary cells: Peeters et al (2008) and Spiga et al (2011)). Moreover, RU486 does not appear to inhibit cortisolactivated translocation.…”
Section: K1mentioning
confidence: 99%
“…These increased HDAC activities in IL-8 promoter site by GRβ may influence the transcription of genes such as IL-8 and benefit to suppress the inflammatory condition, especially in the situation of shortage of glucocorticoid. Recently it was confirmed that GRβ bind RU-486, glucocorticoid antagonist, as an ligand and GRβ bound with RU-486 can regulate gene expression, suggesting that GRβ may have some physiological roles other than as an just bystander or inhibitor of GRα (Lewis-Tuffin et al, 2007). The effect of GRβ on IL-8 secretion was not significant in our experiments, which may be due to insufficient ability of GRβ to interact with DNA or be recruited to the area near inflammatory cytokine gene.…”
Section: Discussionmentioning
confidence: 41%
“…In support of a dominant-negative function for GRb, resistance to glucocorticoid therapy in leukemia has been associated with high cellular levels of GRb (78). Recent studies, however, suggest that GRb may have a previously unappreciated role in cell signaling and the contribution of relative GRb levels in determining cellular sensitivity to glucocorticoids in individuals undergoing glucocorticoid therapy for malignancies remains unclear (79). The GRg isoform contains a three base insertion in the DBD between exons 3 and 4 that results in addition of arginine between the two zinc fingers of the DBD (80).…”
Section: Glucocorticoid Receptor Isoformsmentioning
confidence: 99%